Construction of asymptotic representations of solutions from the classL?? for systems of differential equations by the method of characteristic matrix functions - Ivanyuk, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
For solutions of a system of $q$-linear $n$-order differential equations with singularity rank $p/r,\quad p,r \in \mathbb{N}$. the asymptotic representations are constructed in a sector of the complex plane with a central angle that does not exceed $π r/p$ by using the method of characteristic matrix functions.